Perspectives on decision making amongst older people with end‐stage renal disease and caregivers in Singapore: A qualitative study - Emeline Han; Victoria Haldane; Joel Jun Kai Koh; Rina Yu Chin Quek; Semra Ozdemir; Eric Andrew Finkelstein; Tazeen Hasan Jafar; Hui‐Lin Choong; Sheryl Gan; Lydia W. W. Lim; Farah Shiraz; Helena Legido‐Quigley (Wiley, 2019)
Abstract Background End‐stage renal disease (ESRD) is increasing both globally and in Asia. Singapore has the fifth highest incidence of ESRD worldwide, a trend that is predicted to rise. Older patients with ESRD are faced with a choice of haemodialysis, peritoneal dialysis or conservative management, all of which have their risks and benefits. Objective This study seeks to explore perspectives on decision making amongst older (≥70) Singaporean ESRD patients and their caregivers to undergo (or not to undergo) dialysis. Design Qualitative study design using semi‐structured interviews. Setting and participants Twenty‐three participants were recruited from the largest tertiary hospital in Singapore: seven peritoneal dialysis patients, five haemodialysis patients, four patients on conservative management and seven caregivers. Results While some patients believed that they had made an independent treatment decision, others reported feeling like they had no choice in the matter or that they were strongly persuaded by their doctors and/or family members to undergo dialysis. Patients reported decision‐making factors including loss of autonomy in daily life, financial burden (on themselves or on their families), caregiving burden, alternative medicine, symptoms and disease progression. Caregivers also reported concerns about financial and caregiving burden. Discussion and conclusion This study has identified several factors that should be considered in the design and implementation of decision aids to help older ESRD patients in Singapore make informed treatment decisions, including patients' and caregivers' decision‐making factors as well as the relational dynamics between patients, caregivers and doctors.